1998
DOI: 10.1007/bf03401920
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Epitopes in Type 1 Diabetes Autoantigen Tyrosine Phosphatase IA-2: Potential for Mimicry with Rotavirus and Other Environmental Agents

Abstract: The tyrosine phosphatase IA-2 is a molecular target of pancreatic islet autoimmunity in type 1 diabetes. T-cell epitope peptides in autoantigens have potential diagnostic and therapeutic applications, and they may hold clues to environmental agents with similar sequences that could trigger or exacerbate autoimmune disease. We identified 13 epitope peptides in IA-2 by measuring peripheral blood T-cell proliferation to 68 overlapping, synthetic peptides encompassing the intracytoplasmic domain of IA-2 in six at-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
1
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(145 citation statements)
references
References 40 publications
2
136
1
6
Order By: Relevance
“…No significant difference in relative abundance or prevalence was detected between cases and controls ( Table 2). Rotavirus has been identified as a candidate trigger or exacerbating factor for T1D (44,45). We detected rotavirus in multiple subjects, including three cases and six controls (Fig.…”
Section: Changes In the Eukaryotic Virome Suggest Protective Effectsmentioning
confidence: 81%
“…No significant difference in relative abundance or prevalence was detected between cases and controls ( Table 2). Rotavirus has been identified as a candidate trigger or exacerbating factor for T1D (44,45). We detected rotavirus in multiple subjects, including three cases and six controls (Fig.…”
Section: Changes In the Eukaryotic Virome Suggest Protective Effectsmentioning
confidence: 81%
“…However, binding studies are fraught with difficulties in interpretation, because peptides that stimulate CD4 ϩ T cells have dramatically varying affinities for the restricting MHC class II molecules (58,59). Also, the relationship between T cell responsiveness and peptide binding affinity to MHC is extremely complex, with certain weakly binding self-peptides capable of potent T cell stimulation and, sometimes, even induction of autoimmunity (60).…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study reported a few years ago molecular homology between the VP7 protein of rotavirus and T-cell epitopes in the protein tyrosine phosphatase-related IA-2 molecule and in the GAD65 molecule (54). In a prospective study of infants genetically predisposed to type 1 diabetes, the appearance of diabetes-associated autoantibodies was associated with a significant rise in rotavirus antibodies, indicating that rotavirus infections may induce ␤-cell autoimmunity in genetically susceptible infants (55).…”
Section: Potential Triggers Of ␤-Cell Autoimmunity and Type 1 Diabetesmentioning
confidence: 99%